Rancang Bangun Spectrum Analyzer Menggunakan Fast Fouier Transform Pada Single Board Computer - Afandi Nur Aziz Thohari; Agfianto Eko Putra (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2017)
Spectrum analyzer is an instrument device to measure the magnitude of the frequency and the power of signal. It has many benefits, such as used for testing telecommunication devices, determining the allocation of unused frequencies and also for practicum in schools or universities. However, because of these many benefits, the price of this signal measuring equipment soared in the market.As an alternative, a device that can serve as spectrum analyzer yet has an affordable price is invented in the form of the prototype of spectrum analyzer built using a single board computer by applying a fast Fourier transform algorithm. Feedback from the prototype is in the form of radio signal captured using RTL-SDR.The test results showed that the range of frequencies that can be displayed by the prototype is 24 MHz to 1.769 MHz. Then the test results of fast Fourier transform computing on N points showed that the prototype can work smoothly using the N from 512 to 32.768 points. The use of N more than 32.768 points will cause CPU and disk memory overloaded and lead to a slow performance. Finally, comparison of the levels of spectrum was performed using spectrum analyzer Anritsu MS2720T. As a result, it is known that prototype can be used to show the location of the frequency spectrum of the radio signal appropriately.